The Influence of Alcohol Addiction on the Academic Performance of Students in Makerere University Business School, Nakawa Division - Jet Mutetsi (Uganda Christian University, 2025)
The study was on the Influence of alcohol addiction on the academic performance of students in Makerere University Business School, Nakawa Division. The study population for this study were the students and the respondents were twenty in number. The study was guided by the following research objectives; To investigate how the quality of alcohol consumed affects academic performance, to assess how the frequency of alcohol consumption affects the academic performance of students in MUBS Nakawa and To explore the copying mechanisms applied by students addicted to alcohol in managing academic responsibilities. The social learning theory was utilized in the examination and the focus group discussions were used in the process of data collection. The descriptive research design was used by the researcher to complete this research study. The researcher used the different sources of information and these included primary and secondary sources of information. The findings also led to a conclusion that many parents and guardians only focused at supporting the students with funds and demanding improvements in academic performance hence forgetting to monitor what transpires in the lives of their children. The researcher recommended that more research should be done around the institutions of higher learning about drug addiction within the students of institutions with the aim to find out the challenges and factors that influence the students into alcohol addiction to drugs.
Undergraduate